Learning experiences from an online QI fellowship programme during COVID-19 - a qualitative study - Richard A. Powell; Kandazi Sisya; Vimal Sriram; Rowan Myron (BMC, 2024)
Abstract Background During the COVID-19 pandemic in the United Kingdom, multiple aspects of everyday human existence were disrupted. In contrast, almost all levels of educational learning continued, albeit with modifications, including adaptation to virtual-or online-classroom experiences. This pedagogic transition also occurred in the National Institute of Health and Care Research Applied Research Collaboration Northwest London's (NIHR ARC NWL) Improvement Leader Fellowship, an annual programme focusing on quality improvement (QI). This qualitative study aimed to understand how these changes impacted the Fellows' learning experience. Methods We explored the experiences of two cohorts of programme Fellows (n = 18, 2020-2021 and n = 15, 2021-2022) with focus groups, analysed under a constructivist qualitative research paradigm. Results The two primary and four sub-themes that emerged were: Online QI learning experience (benefits and challenges) and Implementing online QI learning (facilitators and barriers). While benefits had three further sub-themes (i.e., digital flexibility, connection between learners, and respite from impact of COVID-19), challenges had four (i.e., lack of interaction, technological challenges and digital exclusion, human dimension, and digital fatigue). While the facilitators had three sub-themes (i.e., mutual and programmatic support, online resource access, and personal resilience), barriers had one (i.e., preventing implementation and lack of protected time). Conclusion Despite challenges to in-person ways of working, online learning generally worked for action-orientated QI learning, but changes are needed to ensure the effectiveness of future use of virtual learning for QI. Understanding the challenges of the translation of learning into action is crucial for implementation learning, gaining insight into how improvement Fellows navigated this translation when learning remotely and implementing directly in their workplace is key to understanding the evolving nature of implementation over the pandemic years and beyond.